Kesan Bahasa Arab Terhadap Penghuraian Isu Makanan Dalam Surah Al-Midah Dan Surah Al An Am, Kajian Dari Aspek Terminologi, Semantik Dan Budaya - Zainur Rijal Abdul Razak; Arnida A. Bakar; Wan Azura Wan Ahmad; Lubna Abd. Rahman (Universiti Sains Islam Malaysia, 2024)
The objective of this research is to investigate the effect of the Arabic language in terms of its terminology, semantic and culture focusing on the issue of food in Quranic surahs of al-Miiidah and al-hCiim. The research also tried to analyse the level of public understanding and their awareness towards halal food. For the first objective, library research method was used to analyse verses fiom the selected surahs regarding the food issue. For the second objective, 300 questionnaire forms were distributed to the respondents consist of iecturers, students, officers, teachers and food producers. These questionnaires were analysed using the Statistical Packages for Social Sciences software (SPSS) which used the descriptive method (frequency and percentage) and crosstabulations. Apart from that, interviews were held with Jabatan Kemajuan Islam Malaysia (JAKIM) and Jabatan Hal Ehwal Agama Islam Negeri Sembilan (JHEAINS) as to achieve the result for the second objective. The findings show that the three aspects of Arabic language that are: terminology, semantic and culture have a close relationship and must be taken into account when discussing the issue of food in both surahs of al-Miiidah and al-An%. The findings of the research also indicate that majority of the community shows great concern on halal food issue and they also observe its development. However, when it is associated with linguistics. factors, it is found that our community has lack of knowledge regarding the roles of terminology, semantic and culture in the interpretation of al-Quran especially on the food issue.